PENENTUAN UMUR SIMPAN CUKA KAKAO MENGGUNAKAN METODE ACCELERATED SHELF-LIFE TESTING (ASLT) DENGAN PENDEKATAN ARRHENIUS - Sukmayanti, Ni Wayan; Ganda Putra, G.P.; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 2 (2018): April, 2018)
Cocoa vinegar is a fermented vinegar produced from a product of cocoa bean fermentation. The aims of this study were to determine quality change of cocoa vinegar during retention and determine its self-life by using Accelerated Shelf-Life Testing (ASLT) method by Arrhenius Equation Approach. This research was conducted by using one factor, and it was storage temperature treatment that consisting of 3 levels, 30, 40 and 50?C. Retention and observation start from 0 week until 16 weeks, with parameters that observe were acetic acid, pH, total suspended solid and turbidity. Cocoa vinegar has decreased quality during storage, at 30?C, 40?C and 50?C. During storage of the three temperatures, the temperature of 50?C suffered the most rapid deterioration with the characteristic of decreasing the acetic acid content by more than 50%, and the increase of pH, total suspended solid and turbidity on the 63rd day. Shelf life of cocoa vinegar by using the characteristic of acetic acid with linear regression equation y = -4624.x + 10.30 with R² = 0.999.at storage from temperature 10, 20, 30, 40, and 50?C respectively were 431 days (14.3 months). 246 days (8.20 months). 146 days (4.86 months). 89 days (2.96 months).and 56 days (1.86 months). Keywords: vinegar of cocoa, self-life prediction, ASLT method